Before and After Convalescent Plasma Therapy for Covid-19 Patients at Jemursari Islamic Hospital : Perbedaan Kadar D-Dimer Plasma Sebelum dan Sesudah Pemberian Terapi Plasma Konvalesen Pada Pasien Covid-19 di Rumah Sakit Islam Jemursari - Rachmayanti, Notrisia; Bermawi, Bastiana; Nugraha, Gilang; Ballihgoo, Hamiduumajid Ballihg (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
The World Health Organization declared Covid-19 as a Public Health Emergency of International Concern in January 2020. Treatment options for Covid-19 are still limited, so the health system is looking for a strategy to deal with Covid-19 by using convalescent plasma therapy. This study aims to analyze differences in plasma D-Dimer levels before and after convalescent plasma therapy. This study is an analytic observational study with a retrospective design approach. D-Dimer data were taken from medical records of Covid -19 patients who received convalescent plasma therapy and were treated at Jemursari Islamic Hospital from January to March 2021. A total of 117 patients received convalescent plasma therapy and D-Dimer examinations were performed. Plasma D-Dimer levels were analyzed using statistical tests and the result was p = 0.227. The results of p > 0.05 can be concluded that there is no difference between plasma D-Dimer levels before and after convalescent plasma therapy in Covid-19 patients treated at Jemursari Islamic Hospital.